2011
DOI: 10.1557/opl.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis of a Long Period Stacking Ordered Phase in Mg-Al-Gd Alloys

Abstract: Crystal structure of a long period stacking ordered (LPSO) phase newly found in Mg-Al-Gd ternary alloys was investigated by scanning transmission electron microscopy (STEM) and transmission electron microscopy (TEM). The Mg-Al-Gd LPSO phase was confirmed to be constructed with 6-layer structural blocks, which is similar to the case of the 18R-type LPSO phases in the other Mg-TM-RE alloys. Atomic resolution high-angle annular dark-field (HAADF) STEM imaging revealed that Gd atoms are enriched in four layers ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…9,10) Before the system reaches the final structure, some intermediate states possibly exist. For example, in an early stage of the microstructure development, rare earth atoms and transition metal atoms in the alloys are randomly distributed on the hcp-Mg lattices.…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Before the system reaches the final structure, some intermediate states possibly exist. For example, in an early stage of the microstructure development, rare earth atoms and transition metal atoms in the alloys are randomly distributed on the hcp-Mg lattices.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the reported stable periodicity for the sample having ¡-Mg + LPSO two phase microstructure is 14H, 15,25) higher cooling rate in the L+¡-Mg region leads to insufficient mixing in the liquid region and formation of LPSO at higher concentration. The peak position corresponding to the in-plane ordering is much lower than the ideal 2 ffiffi ffi 3 p a position, 4) as reported for 6-9 and 1-2 alloys. To examine the profile at the initial state of formation of LPSO during cooling, three profiles are extracted from Fig.…”
Section: ¹1mentioning
confidence: 49%
“…4,7) In contrast, several works using synchrotron radiation 4,16,17) and scanning probe microscopy 22) showed that the periodicity that appears first in the alloy system does not necessarily the most stable one, and the in-plane order structure in the segregated layer may change with time, temperature and composition.…”
Section: Introductionmentioning
confidence: 99%
“…8) Yokobayashi et al found that the completely ordered L1 2 -type structure in the orderdisorder type LPSO structure in MgAlGd alloys. 9) Recently, Egusa et al showed a revised crystalline structure of 18R-and 14H-type LPSO in Mg 97 Zn 1 RE 2 (RE = Y, Er) and Mg 85 Zn 6 Y 9 alloys. 10) Based on the diffuse scattering pattern in the electron diffraction patterns, they concluded that L1 2 -type clusters align in inplane short range order.…”
Section: )mentioning
confidence: 99%